Phospholipid biosynthesis disruption renders the yeast cells sensitive to antifungals - Kundu, Deepika; Hameed, Saif; Fatima, Zeeshan; Pasrija, Ritu (Folia microbiologica, 2020)
To understand the role of phospholipids on Cdr1p (drug exporter)-mediated drug resistance in yeast, the phospholipids biosynthesis genes PSD1, PSD2, CHO2, and OPI3 were deleted in a strain of Saccharomyces cerevisiae already overexpressing Cdr1-GFP of Candida albicans as a heterologous system. The effect of phospholipids biosynthesis gene deletion was analyzed on Cdr1p-GFP-mediated drug resistance as well as its localization. The results indicate that phospholipids biosynthesis disruption makes the cell sensitive to several drugs including fluconazole (FLC), with Δpsd1/Cdr1-GFP being worst affected. Interestingly, unlike sterols and sphingolipids, the localization of Cdr1p was unaffected by phospholipid biosynthesis gene disruption. Concomitantly, phospholipids mutants also showed an increase in reactive oxygen species (ROS) generation, as verified by fluorescence probe 2',7'-dichlorodihydrofluorescein diacetate (DCFH-DA) method. In addition, the sensitivity of phospholipid mutants with FLC was found to be synergistic to ROS generation, resulting in further reduction of growth. Thus, this study proposes phospholipid biosynthesis as a novel target for antifungal therapy.
Keywords: membránové transportní proteiny; ATP-Binding Cassette Transporters; Candida albicans; Microbial Sensitivity Tests; Antifungal Agents; karboxylyasy; fosfatidylethanolamin-N-methyltransferasa; ROS; Carboxy-Lyases; antifungální látky; mikrobiální testy citlivosti; Azoles; Phosphatidylethanolamine N-Methyltransferase; Membrane Transport Proteins; biosyntetické dráhy; Gene Deletion; delece genu; fungální proteiny; Phospholipids; Drug resistance; Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; Antifungals; Overexpression; mnohočetná fungální léková rezistence; Biosynthetic Pathways; mitochondriální proteiny; Drug Resistance, Multiple, Fungal; pABC3; ABC transportéry; Mitochondria; fosfolipidy; Mitochondrial Proteins; Saccharomyces cerevisiae Proteins; Heterologous expression; Fungal Proteins